A systematic review of behaviour change techniques within interventions to prevent return to smoking postpartum. (May 2019) - Brown, Tracey J.; Hardeman, Wendy; Bauld, Linda; Holland, Richard; Maskrey, Vivienne; Naughton, Felix; Orton, Sophie; Ussher, Michael; Notley, Caitlin
Abstract: Introduction: There is no routine support to prevent postpartum smoking relapse, due to lack of effective interventions. Previous reviews have identified behaviour change techniques (BCTs) within pregnancy cessation trials to specify which components might be incorporated into more effective interventions, but no reviews have identified BCTs for prevention of smoking relapse postpartum. We reviewed BCTs and potential delivery modes, to inform future interventions. Methods: We searched Medline and EMBASE from January 2015–May 2017; and identified trials published before 2015 by handsearching systematic reviews. We included RCTs where: i) ≥1 intervention component aimed to maintain smoking abstinence versus a less intensive intervention; ii) participants included pregnant or postpartum smoking quitters; iii) smoking status was reported in the postpartum period. We extracted trial characteristics and used the Behaviour Change Technique Taxonomy v1 to extract BCTs. We aimed to identify 'promising' BCTs i.e. those frequently occurring and present in ≥2 trials that demonstrated long-term effectiveness (≥6 months postpartum). Data synthesis was narrative. Results: We included 32 trials, six of which demonstrated long-term effectiveness. These six trials used self-help, mainly in conjunction with counselling, and were largely delivered remotely. We identified six BCTs as promising: 'problem solving', 'information about health consequences', 'information about social and environmental consequences', 'social support', 'reduce negative emotions' and 'instruction on how to perform a behaviour'. Conclusions: Future interventions to prevent postpartum smoking relapse might include these six BCTs to maximise effectiveness. Tailored self-help approaches, with/without counselling, may be favourable modes of delivery of BCTs. Registration: PROSPERO CRD42018075677. Highlights: First review of behaviour change techniques to prevent postpartum smoking relapse. Six promising behaviour change techniques (BCTs) were frequently coded. BCTs were problem solving, social support, information about consequences. How to perform a behaviour and reduce negative emotions were also promising BCTs.